Portret Stanisława Staszica w opowiadaniu Mary Hoare pt. Nie sądź - Laskowski, Maciej (Biuletyn Historii Wychowania, 2023)
The subsequent study expands upon the connections between Stanisław Staszic and English literature. Specifically, the paper portrays the Polish Enlightenment thinker as an inspiration of Mary Anne Hoare’s short story entitled Judge not! (Polish Nie sądź) with Staszic as its main protagonist. The ensuing presentation appears very important to many readers, including scholars who (falsely) attribute the story’s authorship to Charles Dickens. The research aims to verify if the idiosyncrasies conveyed by Hoare in her narrative were actually the Pole’s characteristics. At this point, the paper examines the specifics attributed by the Irish authoress to Staszic specifically, making him the focal point of her work. In order to accomplish the set goals, the behind the scenes and the essence of Hoare’s work have been illustrated. Finally, I hope that the article will help to promote the story which has nearly slipped into oblivion and to underline Staszic’s multifaceted activity and life. It has earned him a place in English literature through the pen of a female writer from Ireland.